Method for enhancing interface bonding and corrosion resistance of basalt fiber composite material

By desalinating the surface of the basalt fiber, polydopamine self-polymerization and ZIF-8 modification, and hot-pressing with epoxy resin, the problem of low bonding strength between the basalt fiber and the resin matrix is ​​solved, and the mechanical properties and corrosion resistance of the composite material are significantly improved.

CN119775603AActive Publication Date: 2025-04-08SOUTHWEST PETROLEUM UNIV

Patent Information

Application Number
CN202510295155.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-08
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

The surface energy of the basalt fibers is low and the hydrophilicity is poor, resulting in a low interface bonding strength with the resin matrix, affecting the mechanical properties and durability of the composite material.

Method used

ZIF-8 material was generated by desalinating the surface of the basalt fibers in sequence, self-polymerization of polydopamine, impregnating zinc salt and 2-methylimidazole solution, and finally forming with epoxy resin, which significantly enhances the interface bond strength between the fiber and the resin matrix.

Benefits of technology

The interface bonding force between basalt fibers and epoxy resin is significantly improved, the mechanical properties and corrosion resistance of composite materials are improved, and the better mechanical stability is shown in particular in corrosive environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775603A_ABST
    Figure CN119775603A_ABST
Patent Text Reader

Abstract

The invention provides a method for enhancing interface bonding and corrosion resistance of a basalt fiber composite material, and belongs to the field of fiber surface modification chemical methods. The method is realized through the following steps: firstly, treating basalt fibers by utilizing an organic solvent through high-temperature reflux to prepare desized basalt fibers; then, the desized basalt fibers are immersed in a dopamine solution to be subjected to auto-polymerization, and basalt fibers with a polydopamine coating are prepared; sequentially immersing the basalt fiber coated with the polydopamine into a zinc salt solution and a 2-methylimidazole solution, so as to prepare a ZIF-8 modified basalt fiber; and finally, mixing the ZIF-8 modified basalt fiber with resin through electrostatic coating, and molding by adopting a segmented hot-pressing method to obtain the basalt fiber composite material. According to the method, a composite structure formed by the synergistic effect of a dopamine self-polymerization layer and ZIF-8 is introduced into the surface of the basalt fiber, so that the interface bonding force between the fiber and resin and the corrosion resistance of the composite material are greatly enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fiber surface modification chemistry, and in particular relates to a method for enhancing the interface bonding and corrosion resistance of a basalt fiber composite material. Background Art

[0002] As a new type of high-performance fiber, basalt fiber (BF) has gradually replaced glass fiber and carbon fiber in many engineering fields due to its excellent mechanical properties, high temperature resistance, acid and alkali resistance and good corrosion resistance, and has become an important choice for future composite materials. However, when basalt fiber is combined with a resin matrix, due to its low surface energy and poor hydrophilicity, the interfacial bonding strength between it and the resin matrix is ​​low, which affects the overall mechanical properties and durability of the composite material. Therefore, how to improve the interfacial bonding strength and corrosion resistance of basalt fiber and resin matrix through surface modification has become an important direction of current research.

[0003] The surface of basalt fiber is smooth and chemically inert, resulting in poor bonding between it and the matrix material, which is not conducive to the stress transfer in the matrix to the fiber, thus limiting the effective reinforcement of basalt fiber. At present, the commonly used fiber surface modification methods include physical methods (such as plasma treatment, spraying method) and chemical methods (such as surface solvent treatment, chemical impregnation, etc.). Although these methods can improve the surface properties of the fiber to a certain extent, there are still some limitations, such as complex processing process, unstable effect or poor adaptability to the environment. Therefore, it is of great theoretical and practical significance to develop an efficient, simple, environmentally friendly modification method that can significantly improve the interface bonding and corrosion resistance of basalt fiber composites.

[0004] Therefore, the present invention proposes a method for composite modified basalt fiber based on dopamine and ZIF-8, wherein the surface of basalt fiber (BF) is sequentially desizing, polydopamine self-polymerized, impregnated with zinc salt and 2-methylimidazole solution to generate ZIF-8 material, and finally hot-pressed with epoxy resin, which significantly enhances the interfacial bonding strength between basalt fiber and resin matrix, and exhibits better corrosion resistance in a corrosive environment. This modification method is not only simple and efficient, but also environmentally friendly and has a high application prospect, and is of great significance for enhancing the long-term durability and engineering safety of composite materials. Summary of the invention

[0005] The purpose of the present invention is to effectively solve the defects of chemical inertness of basalt fiber surface and weak interface interaction between basalt fiber and resin matrix, improve the bonding strength between basalt fiber surface and resin matrix and enhance the corrosion resistance of basalt fiber composite material, and provide a method for enhancing interface bonding and corrosion resistance of basalt fiber composite material.

[0006] The technical solution provided by the present invention to solve the above technical problems is: a method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials, comprising the following steps: S1, after basalt fiber is placed in an organic solvent and refluxed at high temperature, it is washed and dried to obtain desized basalt fiber, and then tris(hydroxymethyl)aminomethane) buffer is added to dopamine hydrochloride solution and the pH is adjusted to 8.5, and after ultrasonic dispersion, the desized basalt fiber is immersed in the solution, reacted, washed, and dried to obtain polydopamine coated basalt fiber; S2, immersing the polydopamine-coated basalt fiber obtained in S1 into a zinc salt solution for low-temperature reaction, washing, and drying to obtain zinc salt-soaked basalt fiber; S3, immersing the basalt fiber soaked with zinc salt obtained in S2 into a 2-methylimidazole solution, reacting at a constant temperature, washing, and drying to obtain a ZIF-8 modified basalt fiber; S4, mixing the epoxy resin and the curing agent, adding a catalyst, and vacuum degassing for later use; S5. Electrostatically apply the mixture of the resin and the curing agent obtained in S4 to the surface of the ZIF-8 modified basalt fiber obtained in S3, then lay the electrostatically coated basalt fiber on a mold, and then obtain a basalt fiber composite material by a segmented hot pressing method.

[0007] A further technical solution is that in step S1, the organic solvent is acetone and ethyl acetate in a volume ratio of 3:1; the mass ratio of desized basalt fiber to dopamine solution is 1:50, the reaction temperature is 40°C, the stirring speed is 500rpm, the reaction time is 8 hours, and the polydopamine coverage rate reaches more than 80%.

[0008] A further technical solution is that the solute of the zinc salt solution in step S2 is zinc nitrate hexahydrate, the solvent is methanol, the concentration is 0.15-0.3 mol / L, the stirring speed is 300 rpm, the stirring time is 1 hour, the stirring temperature is 40°C, the immersion reaction time is 6-9 hours, the immersion reaction temperature is 5°C-10°C, the whisker length is 100-300 nm, the diameter is 20-50 nm, and the whisker surface roughness Ra is 50-80 nm.

[0009] A further technical solution is that the solute of the 2-methylimidazole solution in step S3 is 2-methylimidazole, the solvent is a methanol solution, the concentration is 0.2-0.4 mol / L, the stirring speed is 300 rpm, the stirring time is 1 hour, the soaking reaction time is 6-9 hours, and the reaction temperature is 50°C.

[0010] Furthermore, in step S3, the crystal particle size of the ZIF-8 is 50-200nm; the molar ratio of zinc ion (Zn²⁺) to 2-methylimidazole is 1:1.5-1:2.5; the thickness of the ZIF-8 modified layer is 2-5μm, the surface roughness of the ZIF-8 modified basalt fiber is 0.3-0.5μm, the pH value is 5.5-6.0, and the ZIF-8 coverage rate reaches 90%.

[0011] A further technical solution is that the epoxy resin in step S4 is E51 epoxy resin, the catalyst is calcium oxide (CaO), the curing agent is methyltetrahydrophthalic anhydride, the mass ratio of the epoxy resin to the curing agent is 10:8, and the mass ratio of the calcium oxide (CaO) to the total mass ratio of the epoxy resin and the curing agent is 0.1-0.5%; Furthermore, in step S4, the stirring speed is 300 rpm, the stirring temperature is 35°C, and the stirring time is 30 minutes; the vacuum defoaming is divided into two steps, the first step has a vacuum degree of 10MPa and a time of 10-15 minutes, and the second step has a vacuum degree of 5MPa and a time of 5-10 minutes.

[0012] A further technical solution is that the coating viscosity of the electrostatic coating technology in step S5 should be controlled at 150-250 mPa·s (measured at 25°C), the electrostatic voltage of the spray gun is 20-30 kV, the coating thickness is controlled at 50-70 μm, the distance between the spray gun and the surface of the basalt fiber should be 15-25 cm, the spraying air pressure is set to 0.2-0.5 MPa, the coating temperature should be 25-35°C, and the humidity of the electrostatic coating is 40-60%.

[0013] Furthermore, in step S5, the basalt fibers are laid on the mold in layers in an alternating manner with staggered angles of 15° / 60° and 60° / 90° between each layer.

[0014] Furthermore, the segmented hot pressing method in step S5 is divided into three stages, the first stage is the pre-curing stage, the pressure is 0.5MPa, the temperature is 80°C, and the time is 30 minutes; the second stage is the temperature and pressure increase stage, the first pressure is increased to 2MPa, the temperature is increased to 120°C, the second pressure is increased to 5MPa, the temperature is increased to 150°C, and both pressure increases are maintained for 1 hour; the third stage is the temperature reduction and constant pressure stage, the pressure is 5MPa, and the temperature ends at room temperature, the interface porosity of the composite material is ≤0.5%, and the pore size is ≤5μm.

[0015] The second technical problem to be solved by the present invention is to provide a basalt fiber composite material prepared by the above method and having enhanced interface and corrosion resistance of the basalt fiber composite material.

[0016] The present invention has the following beneficial effects: (1) The present invention uses an innovative method of combining dopamine self-polymerization with metal organic framework (ZIF-8) modification, and utilizes the strong adhesion of polydopamine and the chelation of polydopamine and zinc ions (Zn²⁺) to make ZIF-8 grow in situ on the surface of basalt fiber, forming a dual interface reinforcement structure of chemical bonding and nano-scale mechanical interlocking. This modification method significantly improves the interfacial bonding force between basalt fiber and epoxy resin, and improves the mechanical properties of the composite material, especially the mechanical stability in corrosive environments.

[0017] (2) Traditional fiber-reinforced composite materials often fail quickly in harsh environments due to lack of sufficient corrosion resistance. The present invention utilizes the anti-corrosion properties of ZIF-8, and successfully introduces polydopamine to the surface of basalt fiber by chemical bonding with zinc ions (Zn²⁺) and mechanical interlocking of polydopamine and ZIF-8, thereby enhancing the corrosion resistance of the composite material while improving the material interface bonding strength. Especially in corrosive environments such as seawater, the durability of the composite material is greatly improved, extending its service life.

[0018] (3) The modified materials (dopamine, ZIF-8, etc.) used in the present invention have good compatibility with basalt fibers, which not only do not affect the original properties of the fibers, but also enhance their functional performance in the composite materials. Different from traditional fiber-reinforced composite materials, the composite materials modified by this method have enhanced mechanical properties, corrosion resistance and durability, meeting the high performance requirements of modern engineering materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a preparation flow chart of the present invention; Figure 2 This is a scanning electron microscope image of desized basalt fiber; Figure 3 This is a scanning electron micrograph of ZIF8-modified basalt fibers; Figure 4 The single fiber tensile strength diagram of basalt fiber with or without dopamine-assisted ZIF-8 modification; Figure 5 The interfacial shear strength diagram of basalt fiber modified with or without dopamine-assisted ZIF-8; Figure 6 Atomic force microscopy images of the basalt fiber surface before and after ZIF-8 modification; Figure 7 The interfacial shear strength diagram of basalt fibers modified with different concentrations of ZIF-8; Figure 8 The bending strength diagram of basalt fiber composites before and after ZIF-8 modification; Fig. 9 The bending strength retention diagram of basalt fiber composites before and after ZIF-8 modification under seawater corrosion; DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the embodiments and drawings.

[0021] Example 1

[0022] like Figure 1 As shown, the present invention provides a method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials, which is prepared by the following steps: S1. The basalt fiber is placed in an organic solvent of acetone and ethyl acetate in a volume ratio of 3:1 and refluxed at high temperature to obtain a desized basalt fiber. Subsequently, tris(hydroxymethyl)aminomethane) buffer is added to a dopamine hydrochloride solution and the pH is adjusted to 8.5. Then, dopamine self-polymerization is carried out according to a mass ratio of the desized basalt fiber to the dopamine solution of 1:50. The reaction time is 8 hours, the reaction temperature is 40°C, the stirring speed is 500 rpm, and the dopamine-coated basalt fiber is obtained after ultrasonic dispersion, washing, and drying. S2, immersing the polydopamine-coated basalt fiber obtained in S1 in a zinc salt solution with a concentration of 0.2 mol / L for 8 hours at a reaction temperature of 8°C, wherein the solute of the zinc salt solution is zinc nitrate hexahydrate and the solvent is methanol, and the solution is maintained at a temperature of 40°C and a stirring speed of 300 rpm for 1 hour. After the reaction, washing and drying are performed to obtain the zinc salt-soaked basalt fiber; S3, immersing the basalt fiber soaked with zinc salt obtained in S2 in a 0.3 mol / L 2-methylimidazole solution, and reacting at a constant temperature of 50°C for 8 hours, wherein the solute of the 2-methylimidazole solution is 2-methylimidazole, and the solvent is methanol. The stirring speed is maintained at 300 rpm for 1 hour during the configuration, and after the reaction, the basalt fiber modified with ZIF-8 is washed and dried. S4, E51 epoxy resin and curing agent methyl tetrahydrophthalic anhydride were mixed and stirred in a mass ratio of 10:8, and calcium oxide (CaO) was added in an amount of 0.3% of the total mass of the epoxy resin and the curing agent, and then stirred for 30 minutes at a temperature of 35°C and a stirring speed of 300 rpm, and then kept at a vacuum degree of 10 MPa for 10 minutes, and finally kept at a vacuum degree of 5 MPa for 5 minutes for standby use; S5. Electrostatically apply the mixture of the resin and the curing agent obtained in S4 to the surface of the ZIF-8 modified basalt fiber obtained in S3, wherein the viscosity of the electrostatically applied coating is 200 mPa·s (measured at 25°C), the electrostatic voltage of the spray gun is 25 kV, the coating thickness is 55 μm, the distance between the spray gun and the basalt fiber surface is 18 cm, the spray gas is set to 0.3 MPa, the coating temperature is 25°C, the humidity of the electrostatic coating is 50%, and the basalt fiber is laid on the mold at an angle of 15° / 60 ° and 60° / 90° alternatingly, and then the basalt fiber composite material is obtained by segmented hot pressing. The hot pressing is divided into three stages. The first stage is the pre-curing stage, with a pressure of 0.5MPa, a temperature of 80°C and a time of 30 minutes; the second stage is the temperature and pressure increase stage, with the first pressure increase to 2MPa and the temperature increase to 120°C, and the second pressure increase to 5MPa and the temperature increase to 150°C. Both pressure increases are maintained for 1 hour; the third stage is the temperature reduction and constant pressure stage, with a pressure of 5MPa and a temperature of room temperature.

[0023] The surface morphology of desized basalt fiber is as follows Figure 2 As shown in the figure, the surface is smooth and flat. The surface morphology of the basalt fiber modified by ZIF-8 is as follows Figure 3 and surface roughness such as Figure 4 As shown, a metal organic framework structure of ZIF-8 was formed on the surface of the basalt fiber modified with ZIF-8, and the surface roughness reached 0.38 μm.

[0024] Comparative Example 1 Compared with Example 1, in S1, the desized basalt fiber (named BF), the ZIF-8 basalt fiber directly grown without dopamine treatment (named BF@ZIF-8), and the ZIF-8 basalt fiber regrown after dopamine treatment (named BF-PDA@ZIF-8) were tested for the tensile strength of the single fiber. Figure 5 As shown and the micro drop debonding test as Figure 6 As shown in the figure, the single fiber tensile strength of the basalt fiber modified by dopamine treatment (named BF-PDA@ZIF-8) is 15% higher than that of the basalt fiber directly modified without dopamine treatment (named BF-PDA@ZIF-8), indicating that the active groups on the surface of polydopamine provide growth sites for the growth of ZIF-8. Physically, the adhesion effect of polydopamine makes ZIF-8 more tightly bound to the surface of basalt fiber.

[0025] Comparative Example 2 Compared with Example 1, the concentration ratio of zinc salt solution to 2-methylimidazole solution in S3 was changed to 1:1.5 (named BF-PDA@ZIF-8-1.5), 1:2 (named BF-PDA@ZIF-8-2), and 1:2.5 (named BF-PDA@ZIF-8-2.5), respectively, to explore the effect of the concentration ratio of metal ions and organic ligands in the metal organic framework on the interface of modified basalt fibers. The microdroplet debonding test was performed on the three modified basalt fibers, and the results are as follows: Figure 7 As shown, they are 58.7Mpa, 59.5Mpa and 59Mpa respectively. The strength of the three modified basalt fibers is not much different, and the concentration of the two modified solutions has no significant effect on the modification effect.

[0026] In order to further verify the enhancement of the interfacial bonding effect of ZIF-8 modified basalt fiber composites, basalt fiber reinforced epoxy resin composites were prepared, and bending tests were performed on the basalt fiber reinforced epoxy resin composites before ZIF-8 modification (named BF / EP) and the basalt fiber reinforced epoxy resin composites after ZIF-8 modification (named BF-PDA@ZIF-8 / EP). The test results are shown in Figure 2. Figure 8 shown.

[0027] Comparative Example 3 In order to verify the corrosion resistance of the modified basalt fiber composites, the unmodified basalt fiber composites (named BF / EP) and the basalt fiber composites modified with the concentration of zinc salt solution and 2-methylimidazole solution of 1:2 (named BF-PDA@ZIF-8-2 / EP) were immersed in the simulation for 4 weeks, and the four basalt fiber composites were taken out every week to test the bending properties, such as Fig. 9 As shown in the figure, the mechanical properties of basalt fiber composites before and after ZIF-8 modification in seawater are both on a downward trend. The flexural strength retention rate of the modified basalt fiber composites is 4.25% higher than that of the unmodified basalt fiber composites at each time point, proving that the corrosion resistance of the modified basalt fiber composites is significantly enhanced.

[0028] The above description is not intended to limit the present invention in any form. Although the present invention has been disclosed through the above embodiments, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials, characterized in that: The following steps are involved: S1, after basalt fiber is placed in an organic solvent and refluxed at high temperature, it is washed and dried to obtain desized basalt fiber, and then tris(hydroxymethylaminomethane) buffer is added to dopamine hydrochloride solution, the desized basalt fiber is immersed in the dopamine hydrochloride solution, and then washed and dried to obtain polydopamine coated basalt fiber; S2, immersing the polydopamine-coated basalt fiber obtained in S1 into a zinc salt solution for low-temperature reaction, washing, and drying to obtain zinc salt-soaked basalt fiber; S3, immersing the basalt fiber soaked with zinc salt obtained in S2 into a 2-methylimidazole solution, reacting at a constant temperature, washing, and drying to obtain a ZIF-8 modified basalt fiber; S4, mixing the epoxy resin and the curing agent, adding a catalyst, and vacuum degassing for later use; S5. Electrostatically apply the mixture of the resin and the curing agent obtained in S4 to the surface of the ZIF-8 modified basalt fiber obtained in S3, then lay the electrostatically coated basalt fiber on a mold, and then obtain a basalt fiber composite material by a segmented hot pressing method.

2. A method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials according to claim 1, characterized in that: In the step S1, the organic solvent is acetone and ethyl acetate, and the volume ratio is 3:1; the mass ratio of desized basalt fiber to dopamine solution is 1:50, the reaction temperature is 40°C, the stirring speed is 500rpm, the reaction time is 8 hours, and the polydopamine coverage rate reaches more than 80%.

3. The method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials according to claim 1, characterized in that: The solute of the zinc salt solution in step S2 is zinc nitrate hexahydrate, the solvent is methanol, the concentration is 0.15-0.3 mol / L, the stirring speed is 300 rpm, the stirring time is 1 hour, the stirring temperature is 40°C, the immersion reaction time is 6-9 hours, the immersion reaction temperature is 5°C-10°C, the whisker length is 100-300 nm, the diameter is 20-50 nm, and the whisker surface roughness Ra is 50-80 nm.

4. The method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials according to claim 1, characterized in that: The solute of the 2-methylimidazole solution in step S3 is 2-methylimidazole, the solvent is methanol solution, the concentration is 0.2-0.4 mol / L, the stirring speed is 300 rpm, the stirring time is 1 hour, the soaking reaction time is 6-9 hours, and the reaction temperature is 50°C.

5. The method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials according to claim 1, characterized in that: In the step S3, the crystal particle size of the ZIF-8 is 50-200nm; the molar ratio of zinc ion (Zn²⁺) to 2-methylimidazole is 1:1.5-1:2.5; the thickness of the ZIF-8 modified layer is 2-5μm, the surface roughness of the ZIF-8 modified basalt fiber is 0.3-0.5μm, the pH value is 5.5-6.0, and the ZIF-8 coverage rate reaches 90%.

6. The method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials according to claim 1, characterized in that: The epoxy resin in step S4 is E51 epoxy resin, the catalyst is calcium oxide (CaO), the curing agent is methyltetrahydrophthalic anhydride, the mass ratio of epoxy resin to curing agent is 10:8, and the mass ratio of calcium oxide (CaO) to the total mass ratio of epoxy resin and curing agent is 0.1-0.5%.

7. The method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials according to claim 1, characterized in that: In step S4, the stirring speed is 300 rpm, the stirring temperature is 35°C, and the stirring time is 30 minutes; the vacuum degassing is divided into two steps, the first step is a vacuum degree of 10 MPa, the time is 10-15 minutes, and the second step is a vacuum degree of 5 MPa, and the time is 5-10 minutes.

8. The method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials according to claim 1, characterized in that: The coating viscosity of the electrostatic coating technology in step S5 should be controlled at 150-250mPa·s (measured at 25°C), the electrostatic voltage of the spray gun is 20-30kV, the coating thickness is controlled at 50-70μm, the distance between the spray gun and the basalt fiber surface should be 15-25cm, the spraying air pressure is set to 0.2-0.5MPa, the coating temperature should be 25-35°C, and the humidity of the electrostatic coating is 40-60%.

9. The method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials according to claim 1, characterized in that: In step S5, the basalt fibers are laid on the mold in layers in an alternating manner of 15° / 60° and 60° / 90° staggered angles between each layer.

10. The method for enhancing the interface bonding and corrosion resistance of basalt fiber composite materials according to claim 1, characterized in that: The segmented hot pressing method in step S5 is divided into three stages. The first stage is a pre-curing stage, with a pressure of 0.5 MPa, a temperature of 80°C, and a time of 30 minutes; the second stage is a temperature and pressure increase stage, with the first pressure increase to 2 MPa and the temperature increased to 120°C, and the second pressure increase to 5 MPa and the temperature increased to 150°C, and both pressure increases are maintained for 1 hour; the third stage is a temperature reduction and constant pressure stage, with a pressure of 5 MPa and a temperature of room temperature, and the interface porosity of the composite material is ≤0.5%, and the pore size is ≤5 μm.

Citation Information

Patent Citations

  • Preparation method of multi-scale interface toughened resin-based composite material structure

    CN115816922A

  • Modified basalt flake-coated ZIF-8-epoxy resin composite coating and preparation method thereof

    CN116622272A

  • Preparation method, product and application of ZIF-8 (at) PDA intelligent nano container

    CN118185369A

  • Carbon fiber reinforced plastics using polydopamine and the manufacturing method thereof

    KR1020140121019A

  • Ternary composite material, supercapacitor, and related methods

    US20230187146A1

Cited By

  • Low-temperature-resistant composite roller shutter fabric and preparation method thereof

    CN120776596A

  • Low-temperature-resistant composite roller blind fabric and preparation method thereof

    CN120776596B

  • MOFs / para-aramid pulp composite material as well as preparation method and application thereof

    CN120818238A

  • Insulating composite material for soft sling for live working of power transmission line as well as preparation method and application of insulating composite material

    CN121366785A

  • Insulating composite material for live-line work soft sling of power transmission line and preparation method and application thereof

    CN121366785B